Intention to Adopt and Willingness to Pay: Mass Rapid Transport System in Greater Jakarta, Indonesia - Anwar, Rosiwarna; Salehudin, Imam; Mukhlish, Basuki Muhammad; Ririh, Kirana Rukmayuninda (UI Scholars Hub, 2021)
The objective of this study is to explore and examine supportive factors of Mass Rapid Transport (MRT) implementa- tion in Jakarta, Indonesia. Successful implementation requires proper understanding of which factors are influential to the acceptance of this technology. The population of this study is commuters along the North to South route of Jakarta MRT development site. We conducted the survey in thirteen locations along the track based on the Station Development Plan. We obtained only 392 valid data after the validation and verification process. This study used Factor Analysis (FA) to test the construct validity of the measurement instrument and Path Analysis (PA) to identify significant structural paths between variables. We found that only Attitude and Perceived Usefulness significantly predict Intention to Adopt MRT for private vehicle users, while only Attitude and Subjective Norms significantly predict Intention to Adopt MRT for public transportation users. We found that for current users of private transportation, both Overall Monthly Transport Expenditure and Intention to Adopt have significant influence to the Willingness to Pay. While for current users of public transports, no predictor is significant for their Willingness to Pay.